KOMUNIKASI ORGANISASI KEHUMASAN POLRES PASURUAN - M. Alfin Fatikh; Redi Panuju (Asosiasi Pendidikan Tinggi Ilmu Komuniasi (ASPIKOM) Wilayah Riau, 2018)
In reformation era and digitalization era now people increasingly free to uploade anything in social media. Begal case rampant in Pasuruan of east java to make people restless, when there is a perpetrator of Begal caught by public then recorded and then uploaded and the community who became victims of telling in the social media, so now Pasuruan called is